Mother’s role in maintaining oral health of children under five - Aisyah AR; Zulkarnain (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Oral health in early childhood is strongly influenced by maternal behavior, knowledge, and daily caregiving practices. Mothers play a crucial role in shaping healthy oral hygiene habits, promoting proper toothbrushing techniques, and preventing dental problems such as cavities. In many rural areas, limited access to dental health information and services increases the risk of poor oral health among children under the age of five. This study aimed to describe the role of mothers in maintaining oral health among young children in Guali Village. Methods: This descriptive study employed a cross-sectional approach involving mothers of children under five years of age residing in Guali Village. Data were collected using a structured questionnaire that assessed maternal knowledge, attitudes, and practices related to oral hygiene. Variables included toothbrushing routines, supervision patterns, dietary habits, and access to oral health services. Descriptive statistics were used to summarize the findings. Results: The study revealed that although most mothers recognised the importance of maintaining their children’s oral health, there were gaps in their daily oral health practices. A considerable number of mothers reported inconsistent toothbrushing routines, limited supervision, and inadequate knowledge about proper brushing techniques. Sugary snacks and bottle-feeding habits were also commonly reported, contributing to an increased risk of early childhood caries. Additionally, access to regular dental check-ups remained low due to distance and lack of awareness. Conclusion: The findings suggest that while mothers recognise the general importance of oral hygiene, their actual practices remain suboptimal. Strengthening maternal education and improving access to dental health services are crucial for enhancing early childhood oral health in Guali Village. Community-based interventions are recommended to support sustainable behavior change.